Gladiators in suits : race, gender, and the politics of representation in Scandal - Adams, Simone; Moffitt, Kimberly R.; Jackson, Ronald L., 1970- (Television and popular culture., 2019)
""Gladiators in Suits" is a contributed volume that provides an opportunity to analyze the communication, politics, stereotypes, and genre techniques featured in the television series "Scandal" while raising key questions about the intersections of race, gender, sexuality, and viewing audiences. The essays included range from critical looks at various members of Scandal's ensemble, to in-depth analyses of the show's central themes, to audience reception studies via interviews and social media analysis. Additionally, the volume contributes to research on femininity, masculinity, and representations of Black womanhood on television"--